Dihydroartemisinin induces cell apoptosis through repression of UHRF1 in prostate cancer cells. Issue 1 (January 2022) - Xia, Tong; Liu, Sihao; Xu, Ge; Zhou, Siji; Luo, Ziguo
Abstract : Prostate cancer (PCa) seriously jeopardizes men's health worldwide. Dihydroartemisinin, which is an effective antimalarial agent, has shown potential anticancer effects in various human cancer cell lines, including PCa cells. However, the mechanisms underlying the anticancer activity of dihydroartemisinin are not fully understood. Ubiquitin-like with plant homeodomain and ring finger domain 1 (UHRF1) is highly expressed in a variety of tumors and is negatively correlated with the prognosis of various tumors. We reported previously that UHRF1 is downregulated during apoptosis induced by dihydroartemisinin in PC-3 PCa cells. In this study, we transfected PC-3 cells with lentiviruses containing UHRF1 or shRNA-UHRF1. Then, the cells were treated with dihydroartemisinin at different concentrations. Our data showed that overexpression of UHRF1 promoted cell proliferation and migration in PC-3 cells, inhibited cell apoptosis, increased cell proportion in G2 phase, increased DNA methyltransferase 1 and decreased p16 INK4A expression at mRNA and protein levels. Downregulation of UHRF1 produces the opposite results. Moreover, the phenomena caused by overexpression of UHRF1 were inhibited after dihydroartemisinin treatment. Compared with control cells, cells overexpressing UHRF1 can resist the proapoptotic and antiproliferative effects of dihydroartemisinin to a certain extent. The effects of UHRF1 knockdown were further aggravated by dihydroartemisinin treatment, but no statistically significant effect was observed with increasing drug concentration. Our results suggested that dihydroartemisinin decreases proliferation and migration but enhances apoptosis of PCa cells, likely by downregulating UHRF1 and upregulating p16 INK4A .